2020
DOI: 10.1177/1753193420944705
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar footprints of the distal radioulnar ligaments: a detailed topographical study in 21 cadaveric wrists

Abstract: Understanding of the exact topography of the distal radioulnar ligaments insertions remains limited. An anatomical study was performed in 21 fresh frozen cadaveric wrists, where the superficial and deep ligaments were sequentially transected sharply at their ulnar insertions. The relationships between the distal radioulnar ligament footprints relative to the bony landmarks of the ulnar styloid were digitized. Our study demonstrated that in the coronal plane, the superficial distal radioulnar ligaments inserted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The ulnar fovea has previously been described as the primary attachment site of the TFCC, where fibers of the deep DRUL inserting in a fan-shaped manner near the base of the ulnar styloid. 13,14 A more complex footprint of the DRUL has been described more recently, 19,22 but the main insertion remains in the region of the ulnar fovea. To our knowledge no previous biomechanical study has assessed DRUJ instability in translation with different fragment sizes of the ulnar styloid even though the ballottement test, a test for translational stability, was found to be the most accurate clinical test for DRUJ instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ulnar fovea has previously been described as the primary attachment site of the TFCC, where fibers of the deep DRUL inserting in a fan-shaped manner near the base of the ulnar styloid. 13,14 A more complex footprint of the DRUL has been described more recently, 19,22 but the main insertion remains in the region of the ulnar fovea. To our knowledge no previous biomechanical study has assessed DRUJ instability in translation with different fragment sizes of the ulnar styloid even though the ballottement test, a test for translational stability, was found to be the most accurate clinical test for DRUJ instability.…”
Section: Discussionmentioning
confidence: 99%
“…The tip fracture (►Fig. 4) was performed at 84% of the length of the styloid (marked with the help of the Microscribe) between the insertion of the superficial (starting at 87%) and the deep DRUL (ending at 81%) of the styloid, as assessed in a prior study by Maniglio et al 19 The length was measured with a caliper from the initial point of styloid curvature to the most distal end of the styloid process. The fracture was made from the ulnar to radial side perpendicular with the long axis of the ulna.…”
Section: Tip Fracturementioning
confidence: 99%
“…The terminology used for the ligaments showed some variety with the most commonly used terms being: (distal) dorsal and volar/palmar radioulnar ligaments ( n = 8) (Chidgey et al, 1991; Ekenstam & Hagert, 1985; Ishii et al, 1998; Kleinman & Graham, 1998; Rein et al, 2015; Semisch et al, 2016; Totterman & Miller, 1995; Zhan, Li, et al, 2017), (distal) radioulnar ligaments ( n = 8) (Benjamin et al, 1990; Horiuchi et al, 2020; Maniglio et al, 2020; Nakamura et al, 2001; Nakamura & Yabe, 2000; Saka et al, 2021; Shigemitsu et al, 2007; Shin et al, 2017), triangular ligament ( n = 1) (Nakamura et al, 1996) or proximal ligamentous complex ( n = 1) (Nakamura & Makita, 2000). The origin was defined by some studies at the radial attachment and the insertion at the ulnar attachment (Chidgey et al, 1991; Ekenstam & Hagert, 1985; Maniglio et al, 2020; Totterman & Miller, 1995). While other studies defined the origin at the ulnar attachment and the insertion at the radial attachment (Nakamura et al, 1996; Nakamura et al, 2001; Nakamura & Makita, 2000; Nakamura & Yabe, 2000).…”
Section: Tfcc Componentsmentioning
confidence: 99%
“…According to the study by Shin et al (2017), the attachment of the deep portion was located at the fovea and the attachment of the superficial limb was located at the radial side of the styloid process. Maniglio et al (2020) found that the superficial portion was attached around the distal 13% of the styloid process and therefore covering the tip. The deep portion was found to attach to the fovea, extending to the proximal 81% styloid process (Maniglio et al, 2020).…”
Section: Tfcc Componentsmentioning
confidence: 99%
See 1 more Smart Citation